Singular Points of Tubular Surfaces in Minkowski 3-Space - Karacan, Murat Kemal; Es, Hasan; Yayli, Yusuf (Sarajevo Journal of Mathematics, 2024)
In this paper, we examine singular points of tubular surfaces and its parallel surfaces, which is based on two-parameter spatial motion along a curve in Minkowski 3-space. Related results are presented also. 2000 Mathematics Subject Classification. 53A17, 53A35